2007
DOI: 10.1007/s11255-007-9246-2
|View full text |Cite
|
Sign up to set email alerts
|

Screening for prostate cancer using prostate-specific antigen testing in Japanese men on hemodialysis

Abstract: These findings indicate that hemodialysis patients may have an increased risk of prostate cancer, and that prostate cancer detected in such patients tends to be relatively advanced. Therefore, it would be recommended for hemodialysis patients to undergo PSA testing to screen for prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…16 Furthermore, the age of patients with renal failure has increased with progression in the field of therapy, suggesting a proportional increase in the prevalence of prostate cancer among these patients. 17 Recently, it is also reported that in patients with renal failure age-stratified PSA was higher than in the general population. And the cancer detection rate was increased in patients with renal failure compared to that in patients with normal renal function at specific PSA intervals.…”
Section: Discussionmentioning
confidence: 97%
“…16 Furthermore, the age of patients with renal failure has increased with progression in the field of therapy, suggesting a proportional increase in the prevalence of prostate cancer among these patients. 17 Recently, it is also reported that in patients with renal failure age-stratified PSA was higher than in the general population. And the cancer detection rate was increased in patients with renal failure compared to that in patients with normal renal function at specific PSA intervals.…”
Section: Discussionmentioning
confidence: 97%
“…An active PC screening, especially in dialysis and transplant patients with ESRD is based on the fact that patients with PC-ESRD usually presented at a more advanced clinical stage and a grade ≥2 (47–55.3% and 45%, respectively, in our study). Moreover, they had an increased tumor volume, shown by the percentage of positive biopsy scores, rapid malignant cell proliferation, aggressive biochemical behavior, and a higher susceptibility to infections [ 8 , 19 , 20 ]. Our study also showed that 62.6% of transplanted PC-ESRD patients were diagnosed with locally advanced or advanced PC.…”
Section: Discussionmentioning
confidence: 99%
“…No differences in tumour aggressiveness were noted in our comparative analysis according to GFR levels. A previous study (19) investigated 115 male haemodialysis patients and reported that prostate cancer detected in haemodialysis patients tends to be relatively advanced. Joseph et al.…”
Section: Commentmentioning
confidence: 99%
“…greater increases in tPSA levels (8), no changes in tPSA (9,10) or even lower levels of tPSA (11) as well as increases in fPSA (9,10,(12)(13)(14)(15)(16)(17), especially in older patients. Some investigations reported increased (7,18,19) or similar (20) risk of prostate cancer detection rates. Such differences seem to be induced by age (7,11,18), tPSA levels (8) and degree of decreased renal function (14,20), so all of these factors should be taken into consideration when determining whether performing prostate biopsy is necessary for a patient with CKD.…”
Section: What's Newmentioning
confidence: 99%
See 1 more Smart Citation